2016
DOI: 10.1007/s13244-016-0528-z
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and ultrasound probe decontamination practices in Europe: a survey of the European Society of Radiology

Abstract: ObjectivesAlthough ultrasound (US) is considered one of the safest imaging modalities, concerns have been raised regarding potential infection transmission risks through US procedures. A survey was undertaken by the European Society of Radiology (ESR) to establish infection prevention and control measures in US and to highlight the importance of good medical practice.MethodsAn online survey was sent to all 22,000 full ESR members.ResultsThe response rate of completed surveys was 4.3 % (946 practitioners, 97 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
2
31
0
2
Order By: Relevance
“…Im Jahr 2016 wurde eine europaweite Umfrage der European Society of Radiology veröffentlicht, die unter ihren Mitgliedern die Infektionsprävention bei Ultraschalluntersuchungen erhob [11]. Auch hier zeigten sich große Unterschiede bei den Rückmeldungen.…”
Section: Diskussionunclassified
“…Im Jahr 2016 wurde eine europaweite Umfrage der European Society of Radiology veröffentlicht, die unter ihren Mitgliedern die Infektionsprävention bei Ultraschalluntersuchungen erhob [11]. Auch hier zeigten sich große Unterschiede bei den Rückmeldungen.…”
Section: Diskussionunclassified
“…In a European survey of over 1000 respondents, 11% reported not using a probe cover for every endocavitary ultrasound examination, while 69% and 9% reported using LLD and HLD, respectively. Moreover, 11% declared they cleaned the probe at the end of the session only, without any further cleaning procedure between two TVS scans 6 . In contrast, in a recently-published national questionnaire survey in the USA, most (96%) infection preventionists declared adequate compliance with HLD after endocavitary scan in their facility 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Because adequate ultrasound imaging requires good transducer-toskin contact (or endocavitary or other intracorporeal positioning of a transducer), the potential exists for transmission of infection between patients via transducers. 39,40 Ultrasound gel is another potential means for infection transmission, especially if multi-use gel dispensers are utilised. 39,40 It has been shown that bacterial contamination of ultrasound transducers is significantly higher than that of bus poles and public toilet seats.…”
Section: Ultrasound Infection Preventionmentioning
confidence: 99%
“…39,40 Ultrasound gel is another potential means for infection transmission, especially if multi-use gel dispensers are utilised. 39,40 It has been shown that bacterial contamination of ultrasound transducers is significantly higher than that of bus poles and public toilet seats. 40,41 Survival times for some viruses, bacteria and fungi on dry inert surfaces (including transducer surfaces) can be up to several months, or even longer if the surface is contaminated with coexistent organic material.…”
Section: Ultrasound Infection Preventionmentioning
confidence: 99%
See 1 more Smart Citation